(untitled) (Global Journal of Human-Social Science, 2018)
This paper intends to examine the orientation and mobility practices within the Expanded Core Curriculum The study conceptualises and methodologically sheds light on the practices of orientation and mobility O M within the expanded core curriculum ECC for visually impaired learners O M practices have become significant as these are essential in independence and one of the main components of the expanded core curriculum of visually impaired learners The O M practices are done in the school boundaries by O M experts to facilitate and accommodate visually impaired learners for better independence However owing to these practices but not as part of the expanded core curriculum results are less responsive to visually impaired learner s needs Aziz 2007 Existing research has focused on O M practices which are the integral part of the expanded core curriculum for the independence of visually impaired as most were not conducted to address the O M within the expanded core curriculum for visually impaired learner s Therefore this study attempts to conceptualise the orientation and mobility practices within the expanded core curriculum